Selection of Forages for the Tropics (SoFT) - a database and selection tool for identifying forages adapted to local conditions in the tropics and subtropics - Pengelly, Bruce C.; Cook, Bruce G.; Partridge, I.J.; Eagles, D.A.; Peters, Michael; Hanson, Jean; Brown, S.D.; Donnelly, J.L.; Mullen, B.F.; Schultze-Kraft, Rainer; Franco, A.; O'Brien, R. (2005)
Rising populations and incomes in developing countries are likely to double demand for livestock products by 2020 (Delgado et al. 1999). This strong demand has potential to improve profitability for farmers but will require improved animal feeding in both semi-intensive crop-livestock and more extensive livestock systems. Forages are commonly the most cost-effective option to supply feed demands, particularly for ruminant livestock, but also for pig and poultry production. Selecting the most suitable forages for the local system and conditions is critical. Smallholder and even larger-scale farmers depend heavily on advice from extension and development agencies, and from seed companies, but this advice is often limited by inexperience and the difficulty in accessing reliable information. Expert information on an extensive range of tropical forages is now readily available through the SoFT database.